The ramifications of poor communication in construction projects: Unraveling complex litigation and arbitration - Malik Fahad; Habib M. Mohamad; Muhd F. Sulaiman; Sajiharjo M. Suro (Ital Publication, 2024)
The construction industry is known for its complex and diverse nature, involving several stakeholders. Effective communication plays a vital role in ensuring that everyone involved understands the project goals, schedules, and expectations. However, communication breakdowns can lead to delays, exceeding costs, and disputes that often result in litigation. This study aims to investigate the cause and impact of ineffective communication in construction projects in Sabah, Malaysia, and its contribution to disputes and their frequency to escalate into arbitration or litigation. Utilizing a mixed-methods approach, including a survey questionnaire for construction professionals and supported by a literature analysis, the research reveals challenges and proposes solutions. Leveraging mean and standard deviation, this study quantifies the causes and effects of ineffective communication in construction projects, aiding stakeholder comprehension. Survey results highlight work practice differences as a significant cause (27%) of miscommunication, with 99.12% acknowledging miscommunication issues can lead to disputes. About 82.30% stress the importance of welldefined communication protocols. By identifying issues and proposing mitigation strategies, this study empowers project stakeholders to improve project outcomes and reduces the complexity. Respondents with a good understanding of contract form and acts are slightly well aware of how to handle misunderstandings. Moreover, the research emphasizes the importance of communication tools, well-defined contracts, and collaboration in addressing these communication challenges.